Social Values and Authority in Education: Collaboration between School and Families - Bernal, Aurora; Urpí, Carmen; Rivas, Sonia; Repáraz, Rosario (International Journal about Parents in Education, 2023)
A coordinated approach involving both school and families is essential for education to be successful. Mutual support and the satisfaction to teachers and parents alike are particularly important in the area of education in values. We carry out a pilot study, from which we obtained enough information to design and apply family education programmes in the future. In this paper, we explain the design and implementation of the programme: 1) a brief state of the question and a review of some recent bibliography; 2) the stages in which this pilot project was put into practice; 3) some conclusions will be drawn as a guide for future work in this area. The school with which we made our action-research agreement was San Viator (Vitoria, Spain), an independent school with some public funding. The headmaster, the coordinator, and the school counsellor were the professionals who collaborated directly with our project. The educational goal was to provide guidance for parents with children in years 3 and 4 (aged 8 to 10), and the school itself invited these parents to take part in the programme. Out of 75 families at the school, 40 expressed interest, 26 (fathers and mothers) took part in the diagnosis, and 12 mothers participated in the programme.